Impact of length and radius of carbon nanotubes on flow and heat transfer in converging and diverging channels with entropy generation - Badreddine Ayadi; Rabia Rehman; Basharat Ullah; Hafiz Abdul Wahab; Umar Khan; Taseer Muhammad; Lioua Kolsi; Nejib Ghazouani (Case Studies in Thermal Engineering, 2024)
This research examines the complex interplay between the carbon nanotubes' length and radius and how that affects flow patterns, heat transfer properties, and entropy creation in both convergent and divergent channels. Our research elucidates the mechanisms at play by revealing a crucial link between carbon nanotube dimensions and the efficacy of heat transfer processes. In particular, carbon nanotubes with a longer length have better heat transmission properties, while carbon nanotubes with a smaller radius generate less entropy. From microfluidics to energy-efficient materials, these results show significant promise for optimizing thermal systems and improving performance. This research looks on the differences between the thermal transports of single- and multi-walled carbon nanotubes in water. Thermo physical characteristics of carbon nanoparticles are one of a kind and essential for this purpose. The fluid is assumed to be incompressible and to flow steadily a two-dimensional plane. The effects of thermal radiation on the heat transfer of a water-based fluid in convergent and divergent channels with decreasing and expanding walls have been studied. In order to quickly sketch the equations, the RK-4 method with shooting approach is used, and similarity transformation is employed to reduce their dimensionality. The key factors influencing hydrothermal performance have been visualized through the use of graphs. The production numbers of entropy are also shown and explained at length. The obtained data supports the reliability of the approach used. Surface heat transport was found to be negatively impacted by elongation. Colloidal single-walled carbon nanotube (SWCNT) suspensions in water had higher thermal conductivity than water itself.